3(4x-6)+2=4(3x-4)

Simple and best practice solution for 3(4x-6)+2=4(3x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x-6)+2=4(3x-4) equation:



3(4x-6)+2=4(3x-4)
We move all terms to the left:
3(4x-6)+2-(4(3x-4))=0
We multiply parentheses
12x-(4(3x-4))-18+2=0
We calculate terms in parentheses: -(4(3x-4)), so:
4(3x-4)
We multiply parentheses
12x-16
Back to the equation:
-(12x-16)
We add all the numbers together, and all the variables
12x-(12x-16)-16=0
We get rid of parentheses
12x-12x+16-16=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| .70x=55+.60x | | -20=-5(y+7) | | –3(r+7)+–2=–2 | | -0.2b-18.19=-8.1b+14.61+9.9b | | 2a^2=784 | | 180=(9x-26)+(2x-12)+(4x+43) | | 6*(4+3)=x | | 5w+7=-33 | | (6x+34)+(19x+31)=180 | | Y=x2-18 | | 4w-11=69 | | 105=7(5a+5) | | 45/27=15/x | | 6(4+3)=y | | x-(9-2x)=3(x-5) | | 8n+8-8=32-8 | | 7u-16u-19=-11u+5 | | (x+54)+5=90 | | 7a2+14a+98=8 | | -r+20=-18+4r+13 | | x=6(4+3) | | 5n-8=5n-7 | | 1925=-275t | | 4s−28=4 | | 5x+5+x+3x+5=180 | | 2n-3/4=101/4 | | -5b+5-20=11-7b | | 6m-8=-44 | | 0.48x+1.2=1.56 | | 58=2+3x | | -19.94+1.6m-9.27=17.78+5.3 | | 12h+6-4h=5h+10 |

Equations solver categories